Вобраз героя ў аповесцях Андрэя Федарэнкі (на аснове кніг Ланцуг і Ціша) - Alsztyniuk, Anna (Acta Polono-Ruthenica, 2018)
Andrey Fiedarenka (born in 1959) – author of the books: History of the disease (1989), Misery (1994), Afghan casket (2002), No one’s (2009), The Chain (2012), Silence (2014) and others, winner of many awards, including Jerzy Giedroyc Literary Award. The writer is considered a classic of Belarusian literature. In his artistic work, three basic types of heroes can be distinguished: inhabitants of villages, city dwellers and writers. The presentation of often difficult family relations, differences in characters and life priorities of the heroes become for A. Fiedarenka a pretext for deliberations on the subject of contemporary man’s life, his attitude towards people and nature. In his stories, the writer presents primarily people disappointed with life, lonely, seeking the sense of existence in contact with nature. Only hero-writers can be distinguished from the gallery of poor wretches.